An Efficient Test Relaxation Technique for Combinational & Full-Scan Sequential Circuits - El-Maleh, Aiman H. (2002)
Reducing test data size is one of the major challenges in testing systems-on-a-chip. This problem can be solved by test compaction and/or compression techniques. Having a partially specified or relaxed test set increases the effectiveness of test compaction and compression techniques. In this paper, we propose a novel and efficient test relaxation technique for combinational and full-scan sequential circuits. The proposed technique is faster than the brute-force test relaxation method by several orders of magnitude. The application of the technique in improving the effectiveness of test compaction and compression is illustrated.